Elite School Designation and Housing Prices: Quasi-Experimental Evidence from Beijing, China - Bin Huang; Xiaoyan He; Lei Xu; Yu Zhu (Institute of Labor Economics (IZA), 2020)
We explore recent policy changes which aim to equalize access to elite elementary schools in Beijing, to identify the effect of access to quality education on house prices based on a unique dataset. Using property transaction records from Beijing over the period 2013-2016, we construct a balanced 4-wave panel of residential complexes, each of which linked to its designated primary schools. Whereas the multi-school dicing policy involves randomly assigning previously ineligible pupils to key elementary schools through lotteries, the policy of school federation led by elite schools consolidates ordinary primary schools through alliance with elite schools. Moreover, the designated primary school for a residential complex can change from an ordinary primary school to a key elementary school without involving neighbouring schools in surrounding residential complexes through a "pure" re-designation effect. We allow for systemic differences between the treated and non-treated residential complexes using the Matching Difference-in-Differences (MDID) approach. Our estimates indicate that the effect on house prices of being eligible to enrol in a municipal-level key primary school is about 4-6%, while the premium for being eligible for a less prestigious district-level key primary school is only about 2-3%. Our findings are robust to an alternative measure of primary school prestige based on an unofficial ranking from a popular parenting support website, which is shown to be closely related to the number of awards in academic tournaments.
Keywords: R21; I28; H44; 330; quality school designation; house price premium; Matching DID; China